Mobile device use while crossing the street: Utilizing the theory of planned behavior. (June 2019) - Piazza, Andrew J.; Knowlden, Adam P.; Hibberd, Elizabeth; Leeper, James; Paschal, Angelia M.; Usdan, Stuart
Highlights: Theory of Planned Behavior constructs predict distracted street-crossing intention. Attitude toward the behavior emerged as the strongest predictor of intention. 15.6% of participants report high intention to engage in distracted street-crossing. Abstract: Every year, thousands of pedestrians are killed and tens-of-thousands are nonfatally injured as a result of traffic crashes. The year 2016 holds the record for the most pedestrians killed in one year since 1990. Mobile device use while crossing the street has been associated with unsafe crossing behaviors and gait abnormalities, potentially increasing the risk of pedestrian injury or death. Expanding upon the small body of literature, the present study utilized the theory of planned behavior to guide the development of a questionnaire used to collect data from 480 adults on predictors of intentions to use a mobile device while crossing the street. Questionnaire development involved one round of expert panel review ( N  = 4), subsequent pilot testing of a revised questionnaire, and a test-retest reliability assessment. Results demonstrate that attitude toward the behavior, subjective norm, and perceived behavioral control significantly predicted the intention to use a mobile device while crossing the street in this population. Such a questionnaire can be used in the design and evaluation of TPB-based interventions to decrease distracted mobile device use while crossing the street.